Advances in Thermoelectric Mg3Sb2 and Its Derivatives. Issue 10 (10th July 2018) - Shi, Xuemin; Wang, Xiao; Li, Wen; Pei, Yanzhong
Abstract: Over the past couple of decades, thermoelectric Mg3 Sb2 and its derivatives have attracted increasing attention for thermoelectric applications. This is enabled by the richness in composition for manipulating both electronic and thermal properties and by the intrinsic low lattice thermal conductivity. With existing efforts on these materials, the thermoelectric figure of merit has been significantly improved to compete with conventional thermoelectrics, while many of these materials keep the compositions cheap and less‐toxic elements only. Here, not only the control of defects, band structure, electronic transport properties, and lattice thermal conductivity for these materials, but also the proven strategies on transport property manipulation are summarized. These strategies are well demonstrated for advancing thermoelectric Mg3 Sb2 and its derivatives, and the principles used are believed to be equally applicable for many other thermoelectric materials. In addition, perspectives for possible further advancements in this class of thermoelectric materials are shown. Abstract : Stemming from the intrinsic low lattice thermal conductivity and the richness in composition and band structures, n‐type Mg3 Sb2 and its derivatives p‐type AB2 C2 materials have successfully been advanced to show a promising thermoelectric figure of merit zT as high as ≈1.6 and ≈1.2, respectively. A summary of the control of defects, band structure, electronic transport properties, and lattice thermal conductivity for these materials, as well as proven strategies on transport property manipulation is provided.